2017
DOI: 10.1017/jmo.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Translating innovative practices into organizational knowledge in the public sector: A case study

Abstract: Previous research suggests that innovation is heavily informed by strategic management theories and that there is little engagement with practice-based approaches. A case study of a public sector organization identified as doing something innovative is presented. Four main themes emerged. Two themes, the ‘importance of a mandate’ and the ‘development of trust’, had their foundations in traditional management practices. The others, ‘capacity to challenge the norms’ and ‘boundary spanning’, emerged from practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…Given the challenges to translate good management ideas into practice (see e.g., Ferguson & Blackman, 2017), this study corroborates how and why a framework becomes a common ground for a management realm. In a broad sense, the purpose of a framework in becoming an intersubjective reality is to communicate a shared system of meaning.…”
Section: Discussionsupporting
confidence: 69%
“…Given the challenges to translate good management ideas into practice (see e.g., Ferguson & Blackman, 2017), this study corroborates how and why a framework becomes a common ground for a management realm. In a broad sense, the purpose of a framework in becoming an intersubjective reality is to communicate a shared system of meaning.…”
Section: Discussionsupporting
confidence: 69%
“…Communication (Bearman et al, 2010), collaboration (Beck & Plowman, 2013), learning (Chan et al, 2003), coordination (Newell & Swan), identity (Gray et al, 2019), cohesion (Ferguson & Blackman, 2019), trust (Chen & Wang, 2008) 4. When is leadership occurring?…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ferguson and Blackman (2019) found that boundary spanning was related to team cohesion and performance in top management teams and this relationship was magnified as an increasing number of team members-aside from the CEO-participated in boundary spanning activities. Currently, however, both the extent to which formal versus informal leaders should engage in cross-boundary leadership and the extent to which 'boundary-spanning' behaviors reflect the phenomenon of 'leadership' remain poorly understood.…”
Section: Scouting Activities-whatmentioning
confidence: 99%
See 1 more Smart Citation
“…Não foi à toa então que o tema da memória organizacional passou a gerar pesquisas de caráter instrumental para as organizações, tais como gestão do conhecimento e aprendizagem organizacional (p.e., Argote et al, 2003;Miller & Martignoni, 2016;Liu et al, 2018), inovação (p.e., Olivera, 2000Garud et al, 2011;Ferguson & Blackman, 2017), desempenho individual e organizacional (p.e., Kmieciak, 2019;Laureiro-Martinez et al, 2019) e esquecimento organizacional (p.e., Nissley & Casey, 2002;Rao & Argote, 2006;Casey & Olivera, 2011;Holan, 2011). A memória, para essas pesquisas, serviria como um instrumento de gestão por parte da organização, visando a melhoria do seu desempenho.…”
Section: A Memória Nos Estudos Organizacionaisunclassified